Pengaruh model project-based learning terhadap keterampilan proses sains siswa SMP pada pembelajaran IPA - Farhan Abdillah; Rusdianto; Ulin Nuha (Papanda Publisher, 2026)
This study aims to determine the effect of the Project-Based Learning (PjBL) model on junior high school students’ science process skills in science learning. The research was motivated by students’ low science process skills, as indicated by their limited ability to observe, classify, predict, measure, communicate, and draw conclusions during learning activities. This study employed a quasi-experimental approach using a Non-Equivalent Control Group Design. The sample consisted of 46 eighth-grade students at SMPN 2 Maesan, comprising an experimental class (23 students) taught using the PjBL model and a control class (23 students) taught using conventional learning. Data were collected using a validated science process skills test, supported by observations and interviews. The results showed that the average posttest score of science process skills in the experimental class (78.98) was higher than that of the control class (70.28). The independent sample t-test indicated a significance value of 0.001 (p < 0.05), confirming a significant difference between the experimental and control classes. These findings indicate that the Project-Based Learning model effectively enhances students’ science process skills through contextual, collaborative, and investigative project activities and contributes to improving the quality of science learning at the junior high school level